2016
DOI: 10.1002/pssr.201600173
|View full text |Cite
|
Sign up to set email alerts
|

Light‐induced degradation and regeneration of multicrystalline silicon Al‐BSF and PERC solar cells

Abstract: Light‐induced degradation (LID) is a well‐known problem faced by p‐type Czochralski (Cz) monocrystalline silicon (mono‐Si) wafer solar cells. In mono‐Si material, the physical mechanism has been traced to the formation of recombination active boron‐oxygen (B–O) complexes, which can be permanently deactivated through a regeneration process. In recent years, LID has also been identified to be a significant problem for multicrystalline silicon (multi‐Si) wafer solar cells, but the exact physical mechanism is stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 21 publications
(22 reference statements)
3
12
0
Order By: Relevance
“…The reduction in IQE is the strongest in the ~850 to 1100‐nm wavelength range, which indicates that the degradation occurs in the bulk or at the rear surface. Consistently, earlier studies have suggested that LeTID is mainly a bulk effect . Interestingly, both surface passivation schemes produce nearly identical IQE spectra also in the short wavelength range (both before and after degradation), although it is generally understood that AlO x is unfavorable for phosphorus emitter passivation due to the high density of negative fixed charges in the thin film .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The reduction in IQE is the strongest in the ~850 to 1100‐nm wavelength range, which indicates that the degradation occurs in the bulk or at the rear surface. Consistently, earlier studies have suggested that LeTID is mainly a bulk effect . Interestingly, both surface passivation schemes produce nearly identical IQE spectra also in the short wavelength range (both before and after degradation), although it is generally understood that AlO x is unfavorable for phosphorus emitter passivation due to the high density of negative fixed charges in the thin film .…”
Section: Resultssupporting
confidence: 77%
“…Thus, the reduced LeTID could be at least partly explained by a heavier phosphorus emitter, and hence enhanced gettering, in the b-Si cells, 6 although the defect responsible for the degradation is likely another impurity than Fe. 40,41 This explanation supports the conclusion that LeTID is a bulk effect, as suggested previously, 12,23,24 instead of, eg, deterioration of rear surface passivation.…”
Section: Physical Background For Impact Of B-si On Letidsupporting
confidence: 88%
See 1 more Smart Citation
“…Table 1 shows the comparison between best-case scenarios of the mirrorless and perfect-mirror configuration, for unity and 0.98 PLQY. Additionally, Table 1 compares the overall power output with the use of a 25.6% cell efficiency, silicon heterojunction structure with interdigitated back contacts as the subcell [37]; we also demonstrate the power output possible with this tandem LSC-Si architecture by replacing the subcell with a passivated emitter and rear contact (PERC) Si cell [38].…”
Section: Optimal Case Analysismentioning
confidence: 99%
“…The degradation phase in mc‐Si cells is followed by a regeneration phase. Regeneration has been reported for both PERC and Al‐BSF (aluminium back surface field) solar cells at time scales of about 320 h and 200 h, respectively, under 1‐sun illumination at 90 °C device temperature . However, such long time scales may cause a significant energy yield loss (kWh) in fielded PV modules.…”
Section: Introductionmentioning
confidence: 99%